2015
DOI: 10.1097/acm.0000000000000725
|View full text |Cite
|
Sign up to set email alerts
|

Professional Identity Formation in Medical Education for Humanistic, Resilient Physicians

Abstract: Recent calls for an expanded perspective on medical education and training include focusing on complexities of professional identity formation (PIF). Medical educators are challenged to facilitate the active constructive, integrative developmental process of PIF within standardized and personalized and/or formal and informal curricular approaches. How can we best support the complex iterative PIF process for a humanistic, resilient health care professional? How can we effectively scaffold the necessary critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
184
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(192 citation statements)
references
References 60 publications
2
184
0
6
Order By: Relevance
“…The PIF framework then became a useful guide with which to design instructional activities for students. In an effort to support a healthy PIF, structured reflections and simulations as well as systems level actions were implemented to sustain the focus of medical practice on excellent patient care (Branch et al, 2017;Lesser et al, 2010;Wald et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The PIF framework then became a useful guide with which to design instructional activities for students. In an effort to support a healthy PIF, structured reflections and simulations as well as systems level actions were implemented to sustain the focus of medical practice on excellent patient care (Branch et al, 2017;Lesser et al, 2010;Wald et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-six of these 48 articles did not report any formalised evaluation outcomes (Goodwin 2015, Kemp 2014, Ortega 2011, Wald 2010, Joachim 2008, Kumagai 2008, Boudreau 2007, Meites 2003, Louis-Courvoisier 2003, Frich 2003, Acuna 2003, Murray 2003, Jones 2003, Hawkins 2003, Wear 2003, Fried 2003, Spike 2003, Krackov 2003, Sirridge 2003, Andre 2003, Montgomery 2003, Kirklin 2003, Rizzolo 2002, Sklar 2002, Downie 1997, Self 1990. Of the 22 articles reporting evaluation outcomes, 12 described learner satisfaction outcomes (del Pozo 2005, Wald 2015, Gurtoo 2013, Abdel-Halim 2012, George 2011, Karnad 1999, Shapiro 2003, Newell 2003, Anderson 2003, Lypson 2002, Bertman 1985, Wilson 1980. Only ten articles included any formal method of evaluation or assessment of impact beyond learner satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…Williams et al 33 found limited evidence that administrative changes, such as duty hour reductions, a revised grading system, mindfulness training, and self-development groups, prevented burnout in medical students and residents. Wald et al 34 highlighted the use of a reflective writing e-portfolio as a professional identity development tool, creating opportunities for residents to explore work-life balance, resiliency, and burnout prevention. Like our interventions, this example answers the call for reform of medical education 35 to help individuals become physicians who practice from the heart and mind rather than those who simply do the work of a doctor.…”
Section: Discussionmentioning
confidence: 99%